Neurological aspects of menopause – influence of initiating hormonal replacement therapy. I. Neurodegenerative disorders - M. Kanadys, Wiesław (Menopause Review/Przegląd Menopauzalny, 2003)
The morphological and functional changes inherent to ageing lead to age-related disorders, such as neurodegenerative diseases. Menopause as a part of the ageing process as well as the use of hormone replacement therapy (HRT) may influence the occurrence and progression of diseases of the central nervous system. A number of studies suggested that the use of estrogens after menopause did not appear to affect the risk of developing uncomplicated Parkinson’s disease, although estrogen may have reduced the risk of dementia associated with this disorder. The results of a pilot study indicated worsening of symptoms of multiple sclerosis with the menopause, and the improvement of this disease course in postmenopausal women who had tried hormone therapy. Most studies showed a favorable influence of estrogen therapy on preventing and delaying the incidence of Alzheimer’s disease. However, the role of estrogens in slowing the progression of dementia is still controversial. Future randomized trials are needed to determine whether use of HRT prevents neurodegenerative diseases.